State violence against protesters: Perspectives and trends in use of less lethal weapons - McEvoy, Matthew; Corney, Neil; Parras, Marina; Haar, Rohini (Torture Journal, 2024)
Introduction: In recent years mass protest movements have taken to the streets in many countries across the world. Despite strong international and domestic legal protections for the right to freedom of peaceful assembly and other fundamental human rights, entire assemblies are frequently labelled violent and less lethal weapons are used to disperse them. Methods: This article examines the weapons often used by police against public assemblies. Focusing on striking weapons (batons), chemical irritants, kinetic impact projectiles and stun grenades, the article uses examples from various countries to illustrate how these weapons are being used and the associated human rights and health impacts. Results: Worrying trends identified include the use of dangerous or untested equipment, such as thermal foggers to deploy chemical irritants; the use of inherently abusive weapons, such as whips or sjamboks; and the increasing use of certain types of munitions, specifically indiscriminate kinetic impact projectiles. Discussion: The article seeks to support medical and legal professionals becoming more familiar with the weapons being used in the countries they practice in, the effects of those weapons, and clinical aspects in the presentation and care of those exposed.